Évaluer et rénumérer les compétences - Bélanger, Laurent (Relations industrielles / Industrial Relations, 2000)
The article reviews the book, " Évaluer et rénumérer les compétences," by Valérie Marbach.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Compensation administration; Competencies (Human resources); Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z